A ∼100[my]m-resolution position-sensitive detector for slow positronium - Amsler, Claude; Demetrio, Andrea; Müller, Simon R.; Oberthaler, Markus K.; Zimmer, Christian (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2019)
In this work we describe a high-resolution position-sensitive detector for positronium. The detection scheme is based on the photoionization of positronium in a magnetic field and the imaging of the freed positrons with a Microchannel Plate assembly. A spatial resolution of (88±5)μm on the position of the ionized positronium -in the plane perpendicular to a 1.0 T magnetic field- is obtained. The possibility to apply the detection scheme for monitoring the emission into vacuum of positronium from positron/positronium converters, imaging positronium excited to a selected state and characterizing its spatial distribution is discussed. Ways to further improve the spatial resolution of the method are presented.